The Nearest Level Modulation Strategy for Modular Multilevel Converter - WANG Chu; SONG Pinggang; LI Yunfeng (Kongzhi Yu Xinxi Jishu)
This paper briefly introduces topological structure and work principle of the modular multilevel converters (MMC). The capacitor voltage will be imbalanced due to sub-modules in series of the converter. By using the nearest level modulation method and sorting the capacitor voltages of sub-modules, then, according to the direction of the corresponding current to make sure the switching state of all the submodules, the balance of the capacitor voltage of the sub-modules is realized. The simulation results show that the nearest level modulation method is extremely suitable for large power application.